FIELD EVALUATION OF SOIL PHYSICAL, CHEMICAL AND HYDRAULIC PROPERTY CHANGES CAUSED BY SURFACE WATER APPLICATION: A CASE STUDY OF RUAHA-MBUYUNI IRRIGATION SCHEME, IRINGA, TANZANIA - Tarimo, A. K. P. R.; Kihupi, N. I.; Nnko, A. M. (Tanzania Journal of Engineering and Technology, 2018)
Abstract